Studi Literatur: Faktor-Faktor Motivasi Kerja dalam Upaya Meningkatkan Kinerja Karyawan - Apritama Putra Gafur; Mashita Dayana; Reski Amalia Karim; Evanda Parebong; Chris Dayanti Br. Ginting (Rashid : Journal of Economic, 2025)
This study aims to identify and examine the factors influencing work motivation and its impact on employee performance. The research adopts a qualitative approach through a literature review, analyzing various references such as books, scientific articles, and previous research findings. The study reveals that work motivation is influenced by internal factors (needs, goals, attitudes, abilities, and self-drive) and external factors (compensation, job security, social relationships, supervision, and organizational policies). Based on motivational theories proposed by Maslow, Herzberg, Vroom, Adams, and Skinner, motivation plays a central role in improving performance through the fulfillment of needs, fairness, recognition, and reinforcement of positive behavior. Overall, work motivation is not solely determined by financial aspects but also by intrinsic drives, career development opportunities, and a participative work culture. Therefore, organizations need to develop reward systems and work environments that effectively foster employee performance improvement